Hedonic Value Of Purple Sweet Potato’s (Ipomoea Batatas L) Yogurt During The Covid-19 Pandemic - Meri Meri; Anindita Tri Kusuma Pratita (Science Midwifery, 2021)
The Covid-19 pandemic is a time that needs to further improve the body's endurance, to avoid exposure to viral infections that cause the disease. Efforts to increase endurance can be through exercise, balanced nutrient intake, supplementary supplements, and others. One of the efforts to increase endurance is to consume yogurt as a drink containing good bacteria that play a role in improving endurance. However, at this time, the type of yogurt in the market, the dominance plus flavorings, and synthetic dyes. As, another alternative effort added to yogurt is to add purple sweet potato (Ipomoea batatas L) to provide natural and attractive color, as well as provide antioxidant benefits contained in purple sweet potato so that yogurt is made with enriched purple sweet potato. In fact, applications in the community need to be tested favorite, for yogurt to be accepted by the community. The purpose of this study is to find out the picture of fondness for purple sweet potato yogurt during the Covid-19 pandemic. The method was conducted experimentally with the treatment of P1 only yogurt, P2 contains yogurt and purple sweet potato 50:50, P3 contains yogurt and purple sweet potato 70:30 and P4 contains yogurt and purple sweet potato 80:20. Volunteers were given 4 bottles of yogurt (P1, P2, P3, P4), tasted it then filled out a hedonic value towards the color, aroma, taste, and overall appearance. The points given are 1 (very dislike), 2 (dislike), 3 (less than like), 4 (likes), and 5 (very likes). The hedonic value showed the mean P3 pick was (70:30). In conclusion, yogurt and purple sweet potato that people like is yogurt with yogurt composition as much as 70 parts and purple sweet potato 30 parts.